CO2 capture performance of graphene oxide synthesized under ultrasound irradiation - Sezgin, Deniz; Yilmaz, Muge Sari (GAZI UNIV, 2024)
Nowadays, CO2 capture is a vital technology to notably reduce the uncontrolled released CO2 emissions. CO2 capture using graphene oxide, a derivative of graphene, has become of tremendous interest due to its unique morphology. In this present work, graphene oxide (GrO) was synthesized under ultrasound irradiation according to the modified Hummers' method and its CO2 capture performance was examined. The X-ray powder diffraction (XRD) and Fourier transform infrared (FTIR) analyses were applied to explore the structure of the sample. CO2 capture performance of GrO was examined by performing TG analysis under different temperatures. The CO2 adsorption capacity of GrO was reached up to 1.04 mmol g-1 at 25 degrees C. The experimental data getting from the kinetic study revealed that the Avrami model better described the CO2 adsorption.
Keywords: Graphene oxide; ultrasound; CO2 capture; kinetics; AMINATED GRAPHITE OXIDE; ADSORPTION; COMPOSITES; CARBON; CAO; Engineering